Folding rates studied by a combination of static and time-resolved infrared spectroscopy - Krejtschi, Carsten; Hauser, Karin (My University, 2011)
The time-scales of protein folding events range over many orders of magnitude. In order to understand the complex folding mechanisms, peptides with well-defined secondary structure are often used as model systems as they may be regarded as smallest folding units of proteins. The formation of secondary structure elements occur on the nanosecond to low microsecond time scale. Thus, stopped-flow techniques are too slow whereas pulsed laser techniques are capable to trigger folding processes in nanoseconds and to analyze faster folding events. We study ns-to-ls peptide dynamics by temperature-jump infrared spectroscopy. After initiation of a nanosecond temperature jump, the spectral response is monitored at single wavelengths in the amide I region reflecting the dynamics of the peptide backbone.
Relaxation rates are obtained. The helix-to-coil relaxation of polyglutamic acid is a multi-step process and requires more complex models than two-state kinetics. However, there are kinetic steps that are well described by single-exponential behavior and a two-state model. We demonstrate how equilibrium and time-resolved infrared spectroscopic data can be combined to deduce folding rates.
Keywords: 540